Mechanisms for attracting an international contingent of students to Russian universities in relation to the university, regional and federal levels - M. A. Tanina; V. V. Bondarenko; V. A. Yudina; O. N. Leskina (Вестник университета)
Increasing the export potential of the higher education system is a strategic goal of many developed and developing countries, including Russia. At the same time, attracting foreign students to domestic universities makes it possible to attract foreign intellectual resources, develop international cooperation and diplomacy. During the study, a model of a system for managing the competitiveness of higher education in Russia has been developed, which contributes to attracting an international contingent of students to Russian universities. This system takes into account the influence of global environmental factors and state macro-environment factors. The subject of management in this system is represented by the federal, regional and university levels. For each subject level, methods have been developed to attract an international contingent of students to Russian universities. The object of management in the developed system is the level of competitiveness of higher education in Russia.